Thermal oxidation does not fractionate soil organic carbon with differing biological stabilities. Issue 1 (30th September 2016) - Schiedung, Marcus; Don, Axel; Wordell‐Dietrich, Patrick; Alcántara, Viridiana; Kuner, Petra; Guggenberger, Georg
Abstract: Thermal analysis techniques have been used to differentiate soil organic carbon (SOC) pools with differing thermal stability. A correlation between thermal and biological stability has been indicated in some studies, while others reported inconsistent relationships. Despite these controversial findings and no standardized method, several recently published studies used thermal analysis techniques to determine the biological stability and quality of SOC in mineral soils. This study examined whether thermal oxidation at temperature levels between 200°C and 400°C, combined with evolving gas analysis and isotope ratio mass spectrometry, is capable of identifying SOC pools with differing biological stability in mineral soils. Soil samples from three sites being under Miscanthus (C4 ‐plant) cultivation for more than 17 years following former agricultural cropland (only C3 ‐plant) cultivation were used. Due to natural shifts in 13 C content, young and labile Miscanthus ‐derived SOC could be distinguished from stable and old C3 ‐plant‐derived SOC. The proportion of Miscanthus ‐derived SOC increased significantly with increasing temperatures up to 350°C in bulk soil samples, indicating increasing oxidation of labile and young SOC with increasing temperatures. Use of density fractions to validate the thermally oxidized SOC from bulk soil samples revealed that the thermal oxidation patterns did not reflect the biological stability of SOC. The suggested biologically labile particulate organic carbon (light fraction from density fractionation) was clearly enriched in Miscanthus ‐derived young SOC. The thermal oxidation patterns, however, revealed preferential oxidation of these biologically labile fractions not at low temperatures, but rather at higher temperatures. The reverse was found for the biologically stable mineral‐associated density fraction (heavy fraction). Based on different soil types, it was concluded that the thermal stability of SOC between 200°C and 400°C is not a suitable indicator of the biological stability of SOC and, thus, thermal oxidation is not capable of fractionating SOC pools with differing biological stability.